ANALYSIS OF ECONOMIC GROWTH CYCLES’ SYMMETRY IN THE MAIN ECONOMIC SECTORS OF EURO AREA COUNTRIES - Šidlauskaitė, Brigita; Balčiūnas, Norbertas (Ekonomika, 2012)
Abstract. With the European Union integration growing deeper and Euro area countries having the common currency, excluding possibility of a national monetary policy, academic society has raised a debate on economic stabilization opportunities in individual Euro area countries in case the common monetary policy would prove to be adverse. According to the optimum currency area theory, one of the necessary conditions for the successful functioning of the monetary union is the homogeneity of its countries. The possible economic shocks could have a different impact on the economy of individual Euro area countries in the presence of significant differences in their economy structure. Applying the Hodrick–Prescott method, this study identifies and analyses economic growth cycles in the main economic sectors of the Euro area countries. The results suggest that not all economic growth cycles of the Euro area countries sufficiently correlate with the Euro area average, and one of the predetermining factors is the differences in the economic structure.Key words: asymmetry of economic growth cycle, Euro area, value added structure